ABU BAKR NARSHAKHI’S WORK “THE HISTORY OF BUKHARA” AS AN IMPORTANT SOURCEFOR THE TOPONYMY OF THE MIDDLE CENTURIES - Shamsiyeva, M.X. (Educational Research in Universal Sciences, 2023)
In this article, Abu Bakr Narshakhi’s work ‘The History of Bukhara’ is highlighted as a significant written source providing information about the toponymy, nature, and trade activities of Bukhara and the surrounding cities and villages during the 9th-12th centuries.